2010
DOI: 10.1103/physrevb.81.125209
|View full text |Cite
|
Sign up to set email alerts
|

Stark effect and Franz-Keldysh effect of a quantum wire realized by conjugated polymer chains of a diacetylene 3NPh2

Abstract: Conjugated polymer chains diluted in monomer single crystals of a novel diacetylene, 1,10-bis(diphenylamino)-4,6-decadiyne, represent quantum wires of long range coherence. They di¤er from most polydiacetylenes by their repeat unit that consists of two C 4 units with twisted molecular planes. The resulting modi…cation of exciton and band states is studied by electroabsorption which resolves an increase of the exciton transition energy to 2.399 eV and of the free electron gap to 3.158 eV. The Stark shift of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…In addition, a weak broad band is present at ∼ 3.12 eV, which does not belong to these vibronic progressions. It is shown in the companion paper [38] that this structure corresponds to a weakly bound exciton close to the dissociation threshold, which can be observed here because the larger exciton binding energy displaces farther from the gap energy the overall vibronic progression of the lower energy exciton. Between ambient temperature and 13 K all absorption lines are red-shifted by ∼ 80 meV.…”
Section: B Overall Absorption Spectrum and Its Temperature Dependencesupporting
confidence: 57%
See 2 more Smart Citations
“…In addition, a weak broad band is present at ∼ 3.12 eV, which does not belong to these vibronic progressions. It is shown in the companion paper [38] that this structure corresponds to a weakly bound exciton close to the dissociation threshold, which can be observed here because the larger exciton binding energy displaces farther from the gap energy the overall vibronic progression of the lower energy exciton. Between ambient temperature and 13 K all absorption lines are red-shifted by ∼ 80 meV.…”
Section: B Overall Absorption Spectrum and Its Temperature Dependencesupporting
confidence: 57%
“…Moreover, it will be shown that the chains in this material have the optical properties of highly luminescent quasi-1D systems, as isolated red poly-3BCMU chains do [8,10,37]. But in the DA studied in this paper these properties are shared by all chains in the crystal and are not restricted to a small minority of chains, so studies that were not possible on poly-3BCMU such as electroabsorption as in the attendant paper [38], non linear absorption or pump-probe spectroscopies become feasible. The spectroscopic properties of these chains will be described and discussed in two companion papers, this one and another [38] essentially dealing with the study of electroabsorption.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…[9] Strong exciton binding energies are also observed in conjugated polymer chains, [10] where exciton Stark shifts for high electric fields have been investigated as well. [11,12] In recent sudies on single or few-layer semiconductors, such as transition metal dichalcogenides and black phosphorus, exciton binding energies are found to be on the order of hundreds of meV, [13][14][15][16] which brings the possibility of experimentally observing the Stark effect of their excitons. In this context, the case of black phosphorus, [17][18][19][20][21] a layered material that has recently been fabricated in few-layer form [13] and has a strong potential for technological applications, [19,[22][23][24][25][26] is of special interest.…”
mentioning
confidence: 99%
“…which follows from (10), (13)- (16). We present the required wave function as a superposition of Wannier functions…”
Section: Equations Of Motionmentioning
confidence: 99%